2020
DOI: 10.1093/cvr/cvaa256
|View full text |Cite
|
Sign up to set email alerts
|

The effects of liraglutide and dapagliflozin on cardiac function and structure in a multi-hit mouse model of heart failure with preserved ejection fraction

Abstract: Aims Heart failure with preserved ejection fraction (HFpEF) is a multifactorial disease that constitutes several distinct phenotypes, including a common cardiometabolic phenotype with obesity and type 2 diabetes mellitus. Treatment options for HFpEF are limited, and development of novel therapeutics is hindered by the paucity of suitable preclinical HFpEF models that recapitulate the complexity of human HFpEF. Metabolic drugs, like Glucagon Like Peptide Receptor Agonist (GLP-1RA) and Sodium G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(109 citation statements)
references
References 81 publications
2
83
1
Order By: Relevance
“…The previously mentioned cardiometabolic effects of SGLT2 inhibitors, such as improvement in cardiomyocyte energetics and natriuresis, are desirable in patients with HPpEF. Treatment with dapagliflozin in a mouse model of HFpEF led to improvements in global longitudinal strain and cardiac fibrosis [54]. In our meta-analysis, the pooled results of 4 studies and 3738 patients with HFpEF found a 25% relative risk reduction in the composite outcome of cardiovascular death or HF hospitalizations/urgent visits among those randomized to SGLT2 inhibitors.…”
Section: Article In Pressmentioning
confidence: 65%
“…The previously mentioned cardiometabolic effects of SGLT2 inhibitors, such as improvement in cardiomyocyte energetics and natriuresis, are desirable in patients with HPpEF. Treatment with dapagliflozin in a mouse model of HFpEF led to improvements in global longitudinal strain and cardiac fibrosis [54]. In our meta-analysis, the pooled results of 4 studies and 3738 patients with HFpEF found a 25% relative risk reduction in the composite outcome of cardiovascular death or HF hospitalizations/urgent visits among those randomized to SGLT2 inhibitors.…”
Section: Article In Pressmentioning
confidence: 65%
“…2) We just used one dose of dapagliflozin (1.5 mg/kg/day) for treatment. However, in recent preclinical studies on the cardiovascular protective effects of dapagliflozin, researchers also only used dose of 1.5 mg/kg/day for treatment ( Arow et al, 2020 ; Withaar et al, 2021 ). According to the manufacturer’s instructions and Obermeier’s study ( Obermeier et al, 2010 ), dose of 1.5 mg/kg/day in male rats is equivalent to about 9–19 times the human clinical dose of 10 mg/day calculated according to area under the concentration/time curve.…”
Section: Discussionmentioning
confidence: 99%
“…The factors contributing to HFpEF in contrast to HFrEF have been diverse, including endothelial dysfunction, changes in intrinsic cardiomyocyte stiffness with relaxation abnormalities, LV hypertrophy, and low-grade metabolic inflammation with variable extent of fibrosis and oxidative stress [44][45][46][47]. Moreover, both association and dissociation of Ang II and the NP system with markers of oxidative stress, blood pressure, maladaptive immune and inflammatory response, cardiac hypertrophy and fibrosis have all been reported in the context of preclinical DD and HF resulting from mechanical overload, genetic models of leptin resistance, and inappropriate activation of the RAAS [22,24,[48][49][50]. Cardiac fibrosis, intrinsic stiffness and hypertrophy have all been shown to be caused, in part, by enhanced ROS generation in the cardiovascular tissue [9,51,52].…”
Section: Discussionmentioning
confidence: 99%